Employee Motivation in the Uniformed Services – A Bibliometric Analysis - Szydło, Joanna; Moczydłowska, Zuzanna Sara (Motywacja pracowników w służbach mundurowych − analiza bibliometryczna, 2025)
Aim: This article aimed to systematise knowledge of motivation in the uniformed services and identify directions for future research. Methodology: The bibliometric analysis was conducted using Web of Science and Scopus, focusing on publications from 2004-2024 in English, containing terms like “motivation” and “uniformed services,” “police,” “military,” “border guard,” “fire brigade,” and “prison service.” Results: Motivation in the uniformed services is shaped by structure, hierarchy, brand, legal regu-lations, salary, and organizational mission. Structure and hierarchy support internal motivation through clear roles, promotions, and training. External motivation is enhanced by health protection, psychological support, and rewards. A strong organizational brand fosters pride and identification, boosting both internal and external motivation. Salary serves as a key external motivator and can also reinforce internal motivation when perceived as fair. Implications and recommendations: While adequate pay remains the main motivator, promotion, development, and training also play vital roles. Motivation strategies must align with the organization’s culture and operational specifics to be effective. Customising motivational systems increases engagement, satisfaction, and alignment with organizational goals. Originality/value: The article contains original findings. They are of cognitive and utilitarian value.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 124-139